Assessing Pre-Service Science Teachers' Technological Pedagogical Content Knowledge (TPACK) in the Hybrid Learning Environment - Mat Salleh, Muhamad Furkan; Ahmad Syamil Mohd Basri; Mohamad Hisyam Ismail; Zulinda Ayu Zulkipli; Nabilah Abdullah; Siti Zuraida Maaruf; Lutfia Nur Hadiyanti; Siti Alimah; W. H. Nugrahaningsih (Universitas Negeri Semarang, 2025)
The integration of hybrid learning in science education presents both opportunities and challenges for pre-service teachers, particularly in balancing technological, pedagogical, and content knowledge (TPACK) while embedding 21st-century skills. This study examines pre-service science teachers’ perceptions of their TPACK competencies and ability to integrate critical thinking, creativity, communication, and collaboration in hybrid learning environments. Semi-structured interviews were conducted with twelve purposefully selected pre-service teachers using a basic interpretive qualitative approach. Thematic analysis identified one theme - Teaching in a Hybrid Environment, with two sub-themes: delivering science lessons and integrating 21st-century skills. The participants demonstrated adaptability in using digital tools for instruction; however, inconsistencies in technological proficiency and challenges in pedagogical application suggested more structured training. The findings highlight the importance of professional development programmes that provide targeted support, hands-on digital tool training, and instructional strategies tailored to hybrid science education. This study contributes to educational research on TPACK implementation and enlightens teacher preparation programmes with evidence-based recommendations by addressing these gaps. Aligning with the United Nations Sustainable Development Goal (SDG) 4: Quality Education, it underscores the urgency of equipping future educators with the digital competencies and pedagogical expertise required for evolving teaching environments.